15. CLINICAL CHARACTERISTICS, PARACLINICAL FINDINGS, AND TREATMENT OUTCOMES OF PATIENTS WITH VENTILATOR-ASSOCIATED PNEUMONIA IN THE INTENSIVE CARE UNIT OF MILITARY HOSPITAL 175 (Tạp chí Y học Cộng đồng, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate treatment outcomes of patients with ventilator-associated pneumonia (VAP).Subjects and Methods: This is a cross-sectional descriptive study conducted on 76 patients diagnosed with ventilator-associated pneumonia, treated in the Intensive Care Unit at Military Hospital 175 from November 2023 to December 2024.Results: Among the 76 patients studied, late-onset VAP (≥5 days) accounted for a higher proportion (63.2%) compared to early-onset VAP (
Keywords: Ventilator-associated pneumonia; intensive care; chronic obstructive pulmonary disease